Interplay of hole transfer and host-guest interaction in molecular dyad and triad : ensemble and single-molecule spectroscopy and sensing applications - Wu, Xiangyang (2015)
A new molecular dyad consisting of a Cy5 chromophore and ferrocene (Fc) and a triad consisting of Cy5, Fc, and β-cyclodextrin (CD) are synthesized and their photophysical properties investigated at both the ensemble and single-molecule levels. Hole transfer efficiency from Cy5 to Fc in the dyad is reduced upon addition of CD. This is due to an increase in the Cy5-Fc separation (r) when the Fc is encapsulated in the macrocyclic host. On the other hand, the triad adopts either a Fc-CD inclusion complex conformation in which hole transfer quenching of the Cy5 by Fc is minimal or a quasi-static conformation with short r and rapid charge transfer. Single-molecule fluorescence measurements reveal that r is lengthened when the triad molecules are deposited on a glass substrate. By combining intramolecular charge transfer and competitive supramolecular interaction, the triad acts as an efficient chemical sensor to detect different bioactive analytes such as amantadine hydrochloride and sodium lithocholate in aqueous solution and synthetic urine.